2022
DOI: 10.3389/fimmu.2022.861328
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Metabolism and Immune Activity Reveals Four Subtypes With Therapeutic Implications in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is characterized by metabolic dysregulation and distinct immunological signatures. The interplay between metabolic and immune processes in the tumor microenvironment (TME) causes the complexity and heterogeneity of immunotherapy responses observed during ccRCC treatment. Herein, we initially identified two distinct metabolic subtypes (C1 and C2 subtypes) and immune subtypes (I1 and I2 subtypes) based on the occurrence of differentially expressed metabolism-related progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…We found an overall increase in T cell infiltration and CD8 exhausted T cells in PDK2/PDK3 positive ccRCC. This is in consistence with previous T cell landscape studies of ccRCC, which revealed higher proportion of exhausted CD8 T cell in advanced ccRCC 50 , and reinforces the importance of the crosstalk between metabolism and T cell exhaustion in ccRCC 51 , 52 . Relevant to this, lactate administration in mice was recently associated with CD8 T cell stemness and increased anti-tumor immunity 53 .…”
Section: Discussionsupporting
confidence: 89%
“…We found an overall increase in T cell infiltration and CD8 exhausted T cells in PDK2/PDK3 positive ccRCC. This is in consistence with previous T cell landscape studies of ccRCC, which revealed higher proportion of exhausted CD8 T cell in advanced ccRCC 50 , and reinforces the importance of the crosstalk between metabolism and T cell exhaustion in ccRCC 51 , 52 . Relevant to this, lactate administration in mice was recently associated with CD8 T cell stemness and increased anti-tumor immunity 53 .…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we found that PODNL1 was highly expressed in tumor tissues in 15 types of cancers and its high expression was significantly associated with more advanced stages and poor prognosis in multiple types of cancers. Notably, PODNL1 expressions were also enriched in more aggressive molecular subtypes in various tumors, such as the mesenchymal type of GBM [29] and OV [30], and M3 type of KIRC [31]. Combined with previous studies [14][15][16][17][18], such results indicate that PODNL1 could serve as a novel potential biomarker to guide prognosis predictions and individualized therapies in cancers.…”
Section: Discussionsupporting
confidence: 62%
“…During hepatocarcinogenesis, metabolic reprogramming in the liver leading to deceleration of the tricarboxylic acid cycle and activation of fatty acid oxidation (FAO) provided sufficient ATP for cell proliferation, enhanced chemoresistance, 26 and crosstalk with the immune microenvironment. 27 Overall, CMS1 was defined by higher antigenicity (eg, SNV neoantigens, indel neoantigens, and total neoantigens), elevated co-stimulatory molecular (eg, CD28, CD40 ), and better T cell function states. However, a high rate of metabolism dysfunction in MSC1 gave rise to decreased glucose uptake and lactate accumulation in tumor killer cells, further propelling immune evasion and thereby limiting the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%